2014
DOI: 10.1111/exd.12336
|View full text |Cite
|
Sign up to set email alerts
|

Increased frequencies of CD11b+CD33+CD14+HLADRlow myeloid‐derived suppressor cells are an early event in melanoma patients

Abstract: Myeloid-derived suppressor cells (MDSC) are a heterogeneous cell population characterized by immunosuppressive activity. Elevated levels of MDSC in peripheral blood are found in inflammatory diseases as well as in malignant tumors where they are supposed to be major contributors to mechanisms of tumor-associated tolerance. We investigated the frequency and function of MDSC in peripheral blood of melanoma patients and observed an accumulation of CD11b + CD33 + CD14 + HLA-DR low MDSC in all stages of disease (I-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 26 publications
5
26
0
2
Order By: Relevance
“…S1). Similar to studies in other cancer types, [8][9][10][11][12] we found that increased presence of CD14 C HLA-DR low/neg monocytes in lymphoma correlated with increased disease burden, worse treatment response and decreased survival. 5,13 In addition, decreased presence of these cells is associated with improved clinical response to treatments.…”
Section: Introductionsupporting
confidence: 88%
“…S1). Similar to studies in other cancer types, [8][9][10][11][12] we found that increased presence of CD14 C HLA-DR low/neg monocytes in lymphoma correlated with increased disease burden, worse treatment response and decreased survival. 5,13 In addition, decreased presence of these cells is associated with improved clinical response to treatments.…”
Section: Introductionsupporting
confidence: 88%
“…In contrast with mice, human MDSCs lack the Gr1-like antigen and are still being characterized both biologically and phenotypically. However, as previously shown by others and us, the use of CD33 þ CD11b þ HLA-DR À to define MDSCs in various types of cancer has become very common (11,(15)(16)(17)(18). Within this CD33 þ population, the CD14 þ CD15 low/À CD11b þ MDSCs share characteristic similar to the murine monocytic MDSCs, whereas the CD14 À CD15 þ CD11b þ MDSCs resemble the murine granulocytic subtype (11,12).…”
Section: Introductionmentioning
confidence: 72%
“…S1A; refs. 15,17,18,24). Analysis of blood samples taken before the first ipilimumab treatment showed that the percentages of CD33 þ CD11b þ HLA-DR À MDSCs in the group of patients with melanoma was significantly higher (48.8 AE 2.3, P < 0.0001) as compared with HD (27.9 AE 1.7; Fig.…”
Section: Patientsmentioning
confidence: 88%
See 1 more Smart Citation
“…44 Recently Rudolph et al observed accumulation of CD11b + CD33 + CD14 + HLA-DR −/low MDSCs in all stages of melanoma, including early stage I patients. 45 Moreover, circulating monocytic MDSCs were reported to have the negative impact on survival in patients with advanced melanoma and have independent prognostic value. 46,47 Furthermore, MDSCs inversely correlated with the presence of functional antigen-specific T cells and patients with high MDSCs levels had more PD-L1 T cells and more CTLA-4 expression by regulatory T cells.…”
Section: Discussionmentioning
confidence: 99%